TELAAH PEMBANGUNAN KESEHATAN MASYARAKAT DI KABUPATEN SERANG TAHUN 2016 - Kandung Sapto Nugroho; Agus Sjafari; Arenawati Arenawati (Jurnal Administrasi Publik, 2016)
Health development is basically build quality of human life with the aim ofincreasing awareness, willingness and ability of healthy life for everyone to realize thedegree of public health as high. Problems related to health are the problems facedevery day by the people, and a serious concern for the government. Therefore, the indexmeasuring people's health is one of the efforts to determine the health status and healthproblems in an area. This study aims to describe how the index of health development inSerang District in 2016. The study was a descriptive quantitative research. The resultsshowed that the index of development of Health in Serang District is at 0.7709 with agood category. Of some indicators found that the indicators that need attention are theindicators related to access to water, access to sanitation, diseases caused by poorconditions of hygiene and healthy behavior such as diarrhea and hypertension. Averagepublic behavior that no support is smoking behavior, dental hygiene and handwashingmouth.